Mechanism of Antiwrinkle Finishing of Cotton Fabrics Using Mixed Polycarboxylic Acids - Huaifang Wang; Chuanjie Zhang; Xudong Chu; Ping Zhu (International Journal of Polymer Science)
The kinetics, activation energy, and mechanism of esterification of cotton by mixed polycarboxylic acids, namely, 1,2,3,4-butanetetracarboxylic acid (BTCA) and citric acid (CA), were studied during the curing process of cotton fibers in comparison with the esterification by BTCA alone. The reaction rates of these two polycarboxylic acid finishing systems under different temperatures and the dependency of their reaction rate constants on temperature were studied. Consequently, in the temperature range from 120°C to 180°C, the activation energy of the mixed polycarboxylic acids (BTCA+CA) was obtained as Ea=40.7 kJ/mol, which was slightly lower than that for the BTCA finishing system. The reaction occurring between the carboxylic acid group of BTCA and the hydroxyl group of CA was proposed. To confirm and prove the speculation, experiments were conducted to investigate the changes in wrinkle recovery angle and tensile strength retention by changing the concentration of both the single polycarboxylic acid and mixed polycarboxylic acids. The results show that, besides esterification of cotton fibers, citric acid probably functioned as an extender in the curing process, when it was combined with BTCA.